Genetically determined dietary habits and risk of Alzheimer’s disease: a Mendelian randomization study - Teng, Fei; Sun, Jiahui; Chen, Zheyu; Li, Hao (Frontiers in Nutrition, 2024)
Background Emerging evidence have suggested that dietary habits have potential implication on the development of Alzheimer’s disease (AD). However, elucidating the causal relationship between specific dietary factors and AD risk remains a challenge. Therefore, our study endeavors to investigate the causal association between dietary habits and the risk of AD. Materials and methods We analyzed data on 231 dietary habits sourced from the UK Biobank and MRC-IEU, and AD data obtained from the FinnGen database. Employing a framework based on the classic two-sample Mendelian randomization (MR) study, we utilized the inverse-variance weighted (IVW) method as the primary analysis. Additionally, we conducted Steiger filtering and other methods to mitigate horizontal pleiotropy. The robustness of our overall findings was confirmed through multiple sensitivity analysis methods, and forward MR and reverse MR to address potential reverse causality bias. Results Our study evaluated the causal effect between 231 dietary habits involving over 500,000 participants of European ancestry, and 10,520 AD cases. Only oily fish intake demonstrated a significant protective causal relationship with AD following FDR correction (raw p-value = 1.28e-4, FDR p-value = 0.011, OR = 0.60, 95%CI: 0.47–0.78). Additionally, six dietary habits potentially influenced AD risk, with protective causal effects observed for average monthly intake of other alcoholic drinks (raw p-value = 0.024, FDR p-value = 0.574, OR = 0.57, 95%CI: 0.35–0.93) and tea intake (raw p-value = 0.047, FDR p-value = 0.581, OR = 0.78, 95%CI: 0.603–1.00). Conversely, detrimental causal effects were observed for the average weekly champagne plus white wine intake (raw p-value = 0.006, FDR p-value = 0.243, OR = 2.96, 95%CI: 1.37–6.38), Danish pastry intake (raw p-value = 0.036, FDR p-value = 0.574, OR = 13.33, 95%CI: 1.19–149.69), and doughnut intake (raw p-value = 0.039, FDR p-value = 0.574, OR = 7.41, 95%CI: 1.11–49.57). Moreover, the protective effect of goat’s cheese intake phenotype exhibited statistical significance only in the IVW method (raw p-value<0.05). Conclusion Our results provide genetic support for a protective causal effect of oily fish intake on AD risk. Additionally, average monthly intake of other alcoholic drinks and tea consumption were also related with a lower risk of AD. Conversely, average weekly champagne plus white wine intake, Danish pastry intake, and doughnut intake were causally associated with increased risk of AD.